The efficacy and tolerability of 10mg and 20mg/day isotretinoinin the treatment of acne vulgaris in Iraqi patients - Abdullah, Galawish A. (AL-Kindy College Medical Journal, 2013)
Back ground: Oral isotretinoin is recommendedfor sever nodulocystic acne in the doses 0.5-2mg/kg/day which is usually associated with higherincidence of adverse effects. To reduce theincidence of side-effects and to make it more costeffective,the lower dose regimen of isotretinoin hasbeen used.Aim: To compare the efficacy and tolerability oforal isotretinoin 10mg and 20mg/day in acnevulgaris.Methods: one hundred and twenty patients withacne vulgaris were randomized into two treatmentregimens each consisting of 60 patients. The firstwas treated with 10mg/day and the second groupwith 20mg/day for 24 weeks. Fifty five patientsfrom the first group and 47 patients from the secondgroup who continued the study for 24 week and 8weeks after cessation of therapy. The response ratewas recorded in the form of acne load and acnegrade initially, during treatment and after 8 fromstopping treatment. Side effects were also recordedin both groups.Results: The response rate in both groups wascomparable in mild, moderate, and severe acnevulgaris patients. Frequency and severity oftreatment-related side-effects were significantlyhigher in the second group as compared to the firstgroup.Conclusion: 10mg/dayisotretinoin can be used inthe treatment of mild, moderate and severe acnewith less side effects as compared to 20mg/day.